Assessment of a conical spouted with an enhanced fountain bed for biomass gasification. (1st September 2017) - Lopez, G.; Cortazar, M.; Alvarez, J.; Amutio, M.; Bilbao, J.; Olazar, M.
Highlights: Fountain enhanced spouting regime was developed for biomass gasification. The aim is to increase residence time and gas-solid contact in the fountain region. This regime is stable operating with fine materials and high gas velocities. Temperature has a remarkable effect on fountain enhanced spouting velocity. Several parameters may be fine tuned in order to meet the most suitable conditions. Abstract: This study pursues the development and characterization of a fountain enhanced spouting regime. This novel gas solid-contact method combines the advantages of fountain confined conical spouted beds with those of draft tube conical spouted beds. The aim of confining the fountain, and therefore attaining a clearly differentiated regime, is to progress towards a highly efficient conical spouted bed reactor for biomass gasification. Accordingly, and in order to delve into the knowledge of the regimes attained in this contact method, a study has been conducted by analyzing the influence operating parameters (temperature, gas flow rate, particle size and bed mass) and draft tube geometry (tube diameter and entrainment zone height) have on hydrodynamics. Fountain confinement allows greatly enlarging the fountain region, especially the height, which improves the contact between reacting gases and the catalyst. Moreover, the residence time distribution, and therefore the average residence time, may be optimized by confining and enlarging the fountain zone. These features promote tar cracking and so increase biomass conversion efficiency, which are highly relevant facts for use of conical spouted bed reactors in gasification.